Effect Of Sulfur In Coal Used In Ceramic Industries - C. W. Parmelee (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
THE ideal fuel for burning ceramic wares is the one that, among other characteristics, has little or no sulfur. For that reason wood was long considered the most desirable fuel but its high cost has practically eliminated its used except in regions where it is very abundant or other circumstances warrant its choice. The fuels commonly employed are natural and producer gas, oil, and coal. The last named is undoubtedly the most important, not only in this country but abroad. Occasionally anthracite is used but the larger part is bituminous. The quality of the coal used depends on the kind and the value of the products being manufactured. For some materials, such as common brick, hollow block, etc., the quality of the coal is of less importance than in the manufacture of polychrome terra cotta, pottery, porcelain, etc. It is obvious that in burning clays that contain notable amounts of pyrite, marcasite or gypsum, as is the case with many common clays, the sulfur content of the fuel is of much less importance. The permissible amount of sulfur in the coal used will depend on the kind of product being manufactured. "A good sample' of coal commonly used in pottery ovens has something like this quantity of sulfur." PER CENT. Total sulfur 1.20 Sulfur in the ash 0.11 Volatile sulfur a 1.09